Incomes in East-Central Europe: Distributions, Patterns, and Perceptions - Jirí Vecerník (Luxembourg Income Study (LIS), 1995)
Little is known about what has happened to income distributions in East-Central Europe since 1989, the end of the Communist period. This paper explores how earnings and incomes have changed since the removal of the command economy and the introduction of markets by combining two perspectives: a comparison across time showing how far distribution has changed; and, a cross-country comparison displaying the degree to which country specific differences were maintained or shifted. The author concludes that, in the early 1990s, country specific income distributions and disparities were a result of long-term development rather than of recent changes. In a comparative perspective, the paper finds large differences in inequality throughout East-Central Europe.
Keywords: 330